2016
DOI: 10.1038/ncomms13402
|View full text |Cite
|
Sign up to set email alerts
|

Role of syn-eruptive plagioclase disequilibrium crystallization in basaltic magma ascent dynamics

Abstract: Timescales of magma ascent in conduit models are typically assumed to be much longer than crystallization and gas exsolution for basaltic eruptions. However, it is now recognized that basaltic magmas may rise fast enough for disequilibrium processes to play a key role on the ascent dynamics. The quantification of the characteristic times for crystallization and exsolution processes are fundamental to our understanding of such disequilibria and ascent dynamics. Here we use observations from Mount Etna's 2001 er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 65 publications
2
40
0
Order By: Relevance
“…The model proposed by Annen et al 41 successfully describes the system at physical conditions close to the thermodynamical equilibrium. However, the estimated rising velocities and those reported in the literature for natural systems suggest that the ascending magmas could not be at equilibrium conditions 52 . In particular, La Spina et al 52 indicated that basaltic magmas ascending from ~10 km depth need approximately 2 h to reach the equilibrium crystal volume content.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The model proposed by Annen et al 41 successfully describes the system at physical conditions close to the thermodynamical equilibrium. However, the estimated rising velocities and those reported in the literature for natural systems suggest that the ascending magmas could not be at equilibrium conditions 52 . In particular, La Spina et al 52 indicated that basaltic magmas ascending from ~10 km depth need approximately 2 h to reach the equilibrium crystal volume content.…”
Section: Discussionmentioning
confidence: 65%
“…However, the estimated rising velocities and those reported in the literature for natural systems suggest that the ascending magmas could not be at equilibrium conditions 52 . In particular, La Spina et al 52 indicated that basaltic magmas ascending from ~10 km depth need approximately 2 h to reach the equilibrium crystal volume content. Therefore, when the average ascent velocity is higher than ~1 m s −1 , the system does not have enough time to reach the equilibrium condition, resulting in a delayed crystallization and leading to a lower viscosity of the mixture.…”
Section: Discussionmentioning
confidence: 65%
“…O 10 −1 − 10 0 , and u z,avg = O 10 0 (La Spina et al, 2016), and laminar flow characterises nearly the entire conduit. Thus, assuming that the flow is fully developed and introducing the normalised radiusr = r R and the normalised velocityū = u z (r) u z,max (where u z,max is the maximum velocity), we can write:…”
Section: Analysis Of Magma Residence Time In Conduitsmentioning
confidence: 98%
“…The first mechanism concerns ash accompanying lava fountain activity and generated by fragmentation of fast-rising (order of 10 to 40 m/s, La Spina et al, 2016;Giuffrida et al, 2018), vesiculating magma. Previous studies have well documented that lava fountaining from SEC at Etna is driven by the superposition of two distinct outgassing mechanisms, gas foam collapse and syn-eruptive vesiculation in the glassy pockets between bubble walls (Figure 7) (Allard et al, 2005;Polacci et al, 2006Polacci et al, , 2009Vergniolle and Ripepe, 2008).…”
Section: Mechanism No 1 (The Sustained 4-5 September 2007 Lava Fountmentioning
confidence: 99%
“…The major volatile species, H 2 O, CO 2 , SO 2 , HCl and HF, all have pressure-dependent solubility profiles, producing significant variability in gas composition as a function of pressure in the magmatic system (Lesne et al, 2012) which is then further modulated by the degassing style and magma dynamics (La Spina et al, 2016). The viscosity of magma controls its flow dynamics, and this is in turn controlled by the dissolved water contents of the magma and vesicularity, producing complex non-linear relationships between magma ascent and degassing (Gonnermann and Manga, 2003).…”
Section: Introductionmentioning
confidence: 99%